Characteristics Of Transforming Accounting To Ifrs In Joint Ventures - Yusupov Asror Makhmanazar ugli (Periodica Journal, 2025)
The adoption of International Financial Reporting Standards (IFRS) in joint ventures is a complex process driven by the need for global harmonization and enhanced transparency. This article explores the key features of transforming accounting practices to IFRS in joint ventures, focusing on technical, organizational, and regulatory dimensions. Using a mixed-methods approach, including a literature review and case study analysis, the study identifies critical aspects such as IFRS 11 compliance, stakeholder coordination, and cost management. Results reveal that successful transformation hinges on robust governance, expertise development, and regulatory alignment, while barriers include high implementation costs and jurisdictional disparities. The findings offer practical insights for practitioners and contribute to the literature by addressing joint venture-specific IFRS challenges. The article emphasizes tailored strategies to ensure compliance and improve financial reporting quality in collaborative entities.
Keywords: IFRS; joint ventures; accounting transformation